Abatacept in rheumatoid arthritis and the risk of cancer: a world observational post-marketing study. (27th December 2019) - de Germay, Sibylle; Bagheri, Haleh; Despas, Fabien; Rousseau, Vanessa; Montastruc, François
Abstract: Objectives: We aimed to investigate whether abatacept used in patients for RA was associated with an increased risk of reporting overall cancer and specific cancers, including breast, lung, lymphoma, melanoma and non-melanoma skin cancer when compared with other biologic DMARDs (bDMARDs). Methods: We performed an observational study within VigiBase, the World Health Organization's global database of individual case safety reports, from 2007 to 2017 to compare the cases of cancer reported in RA patients exposed to abatacept with those reported in RA patients exposed to other bDMARDs. We conducted disproportionality analyses allowing the estimation of reporting odds ratios (RORs) with 95% CIs of the exposure odds among spontaneous reporting of cancers to the exposure odds among other reported adverse effects. Results: We identified 15 846 adverse effects reported in RA patients who received abatacept and 290 568 adverse effects reported in RA patients treated with other bDMARDs. Compared with other bDMARDs, the use of abatacept was not associated with an increased risk of reporting cancer overall [ROR 0.98 (95% CI 0.91, 1.05)]. Analyses by specific cancer sites showed a significantly increased ROR for melanoma [1.58 (95% CI 1.17, 2.08)], but not for other specific cancer sites. Conclusion: Compared with other bDMARDs, exposure to abatacept in RA patients was only significantly associated with an increased risk of reporting melanoma. This increased risk is consistent with the properties of abatacept (CTLA-4 agonist) since it has an opposite action than ipilimumab, an antibody that blocks CTLA-4 and is approved for the treatment of malignant melanoma. Trial registration: ClinicalTrials.gov (http://clinicaltrials.gov ), NCT03980639.